Studi Kritis Buku Hazihi Lugati dan al-Muyassar fi Ilmin Nahwi di Pondok Pesantren Tahfizhul Qur’an Imam An-Nasa’i Gowa
This research discusses the critical study of Arabic textbooks at the Tahfizhul Qur’an Imam An-Nasa’i Gowa Islamic Boarding School at the wust